2015
DOI: 10.1007/s10646-015-1498-5
|View full text |Cite
|
Sign up to set email alerts
|

Select metal and metalloid surveillance of free-ranging Eastern box turtles from Illinois and Tennessee (Terrapene carolina carolina)

Abstract: The Eastern box turtle (Terrapene carolina carolina) is a primarily terrestrial chelonian distributed across the eastern US. It has been proposed as a biomonitor due to its longevity, small home range, and reliance on the environment to meet its metabolic needs. Plasma samples from 273 free-ranging box turtles from populations in Tennessee and Illinois in 2011 and 2012 were evaluated for presence of heavy metals and to characterize hematologic variables. Lead (Pb), arsenic (As), zinc (Zn), chromium (Cr), selen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
(32 reference statements)
1
5
0
Order By: Relevance
“…Although females were larger than males (Kruskal-Wallis χ²=19.7449, df = 1, p < 0.01), sex did not influence the concentrations of trace elements (all p > 0.12). This suggests that feeding, metabolism or growth rates were broadly similar for both genders (Allender et al 2015;Yu et al 2011) and that contrarily to what has been shown in another species (Nagle et al 2001) or in sea turtles (Guirlet et al 2008), eggs may not represent a major excretion pathway in female E. orbicularis.…”
Section: Resultssupporting
confidence: 57%
See 2 more Smart Citations
“…Although females were larger than males (Kruskal-Wallis χ²=19.7449, df = 1, p < 0.01), sex did not influence the concentrations of trace elements (all p > 0.12). This suggests that feeding, metabolism or growth rates were broadly similar for both genders (Allender et al 2015;Yu et al 2011) and that contrarily to what has been shown in another species (Nagle et al 2001) or in sea turtles (Guirlet et al 2008), eggs may not represent a major excretion pathway in female E. orbicularis.…”
Section: Resultssupporting
confidence: 57%
“…Most trace elements concentrations did not correlate with body size suggesting that E. orbicularis does not bioaccumulate these contaminants with age as showed in other turtle species (Allender et al 2015;Yadollahvand et al 2014). Yet, and similarly to other studies (Overmann and Krajicek 1995;Nagle et al 2001;Bergeron et al 2007;Yu et al 2011), we found two notable exceptions to this trend: Zn concentrations (in muscle, rs= 0.49, p < 0.05; Fig.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…ranavirus, Mycoplasma sp., herpesviruses, adenovirus) and toxicants (e.g. organochlorines, heavy metals); underscoring the need for reliable tools to characterize emerging health threats [29][30][31][32][33][34][35][36][37][38][39][40]. Acute phase response testing in box turtles may supplement existing diagnostic modalities and improve health assessment protocols; ultimately supporting conservation goals and enhancing the evaluation of ecosystem wellness [41].…”
Section: Introductionmentioning
confidence: 99%
“…all SCL> 96.5 mm corresponding to large juveniles and adults), while a previous study included neonates and very small individuals (see Guillot et al 2018 As already suggested for this species (Guillot et al 2018), and for other freshwater turtles (Adel et al 2005;Bergeron et al 2007;Schneider et al 2009;Turnquist et al 2011;Hopkins et al 2013a;Slimani et al 2018) sex did not influence Hg concentrations. This suggests that feeding, metabolism and/or growth rates are presumably fairly similar for both sexes (Allender et al 2015;Yu et al 2011), contrarily…”
Section: Individual Determinants Of Hg Concentrationsmentioning
confidence: 97%